2005
DOI: 10.1097/01.ju.0000145868.18824.25
|View full text |Cite
|
Sign up to set email alerts
|

Urinary Matrix Calculi: Our Experience at a Single Institution

Abstract: A high index of suspicion is required in diagnosing matrix calculi in addition to carefully selected radiographic imaging. Due to their variable appearance in standard radiological studies, the evaluation of matrix stones may require invasive techniques such as ureteroscopy for accurate diagnosis. Percutaneous removal is the primary treatment modality to render patients stone-free.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
33
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(34 citation statements)
references
References 11 publications
1
33
0
Order By: Relevance
“…If suspicious for these stone compositions based on prior history or crystal presence on urinalysis, SWL is best avoided and another treatment selected. Matrix stones, while not dense, are made of organic matter and do not break with SWL [25] . Ureteroscopy or percutaneous nephrolithotomy should be used to treat this rare stone type if known.…”
Section: Patient Selectionmentioning
confidence: 99%
“…If suspicious for these stone compositions based on prior history or crystal presence on urinalysis, SWL is best avoided and another treatment selected. Matrix stones, while not dense, are made of organic matter and do not break with SWL [25] . Ureteroscopy or percutaneous nephrolithotomy should be used to treat this rare stone type if known.…”
Section: Patient Selectionmentioning
confidence: 99%
“…The radiological appearance of these stones can be variable. Bani-Hani et al [4] reported the presence of gas in the renal pelvis, probably secondary to active infection. Intravenous urography in these patients is often of poor diagnostic value due to impaired renal function, which makes the contrast medium inadequate to outline the filling defects.…”
Section: Discussionmentioning
confidence: 99%
“…Histological examination shows laminar concentric rings of organized matrix with an orderly, layered deposition of mineral. Bani-Hani et al [4] believe that reduced urinary excretion of calcium by the affected kidney is responsible for the lack of calcifications, but it is possible that the normal calcium excretion by the contralateral kidney compensates for the 24-hour urinary calcium amount. Indeed, all our patients were normocalciuric and we did not find any alteration at metabolic screening.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, brushite stone formers should be treated with a paradigm similar to cystine stone formers, and only those patients with small stone burdens should undergo SWL. Finally, matrix calculi, which are composed of as much as 65% organic matter, also respond very poorly to SWL, and should generally be approached through endoscopic means [Bani-Hani et al 2005].…”
Section: Patient Selectionmentioning
confidence: 99%